Development of computerised restricted entry system using bar code reader and personal identification number / Rizarulnizam Hashim - Hashim, Rizarulnizam (1994)
This report is concerned on the investigation of a computerised restricted entry system using bar code reader and personal identification number (PIN). It consists of three major components as will be discussed in this report; namely ; . Bar code reader . Controller . Programming